PENGETAHUAN PERAWAT TENTANG KETEPATAN IDENTIFIKASI PASIEN DI RS. PMC JOMBANG - Edi Wibowo Suwandi; Adi Rizal Arifin (Jurnal EDUNursing, 2018)
ABSTRACT Knowledge is the result of "know" and this happens after the person inserts the sensing. Knowledge or cognitive is a very important domain for the formation of one's actions (behavior Ovent) (Wawan & Dewi, 2011). The purpose of this study was to determine the level of nurse knowledge about accuracy with the right patient, at Rs. Complementary Medikal Center. This research uses Descriptive research design with population of 60 respondents and sample size. 52 respondents who have filled sample and sample technique which is Simple Random Sampling. Then enter the data using a questionnaire filled by the nurse. Then to find out information about how to measure the accuracy between patients. The results show that the research is mostly knowledge of the patient, the current patient, the time before giving the drug and the product, the time before taking the sample and the time before doing the action or good. Therefore, it can be clearly known about the patient appropriately, at Rs. Complementary Medikal Center Jombang. Keywords: Nurse knowledge, patient identification, accuracy.